Old elite are co-opted subdued or oppressed? : The politics of anti-corruption crusade in India in perspective - Pillai, Mohanan B.; Joshy, P.M. (2012)
Finance capital is a catalytic agent of corruption in all walks of life and the political class which sets the legal boundaries of the game has indeed become the protagonists of corruption. The political class has been facing some kind of a legitimacy crisis and the overall developments have generated frustration and insecurity in the common psyche. In this scenario, the anti-graft movement by Anna Hazare could be seen as a tension absorbing systemic movement as also a process of consolidation of cultural capital that facilitates the rehabilitation of traditional elite to the pedestals of power through the construction of a technocratic democracy as neo - liberalism denounces the importance of the Parliament ina democratic system in favour of governance by 'experts' and 'elite'. - Reproduced.
Keywords: Corruption - India; Corruption